Daniel Gallegos: nostalgia, irreverencia y otros placeres - Cortés, María Lourdes (2013)
This article propose a panoramic view of some of the most important works of Daniel Gallegos (novel and drama).Also, we look through several significant topics as the wistfully and the critics of the contemporany society.